Starch Biosynthetic Enzymes from Developing Maize Endosperm Associate in Multisubunit Complexes - Hennen-Bierwagen, Tracie A. (American Society of Plant Biologists, 2008)
Mutations affecting specific starch biosynthetic enzymes commonly have pleiotropic effects on other enzymes in the same metabolic pathway. Such genetic evidence indicates functional relationships between components of the starch biosynthetic system, including starch synthases (SSs), starch branching enzymes (BEs), and starch debranching enzymes; however, the molecular explanation for these functional interactions is not known. One possibility is that specific SSs, BEs, and/or starch debranching enzymes associate physically with each other in multisubunit complexes. To test this hypothesis, this study sought to identify stable associations between three separate SS polypeptides (SSI, SSIIa, and SSIII) and three separate BE polypeptides (BEI, BEIIa, and BEIIb) from maize (Zea mays) amyloplasts. Detection methods included in vivo protein-protein interaction tests in yeast (Saccharomyces cerevisiae) nuclei, immunoprecipitation, and affinity purification using recombinant proteins as the solid phase ligand. Eight different instances were detected of specific pairs of proteins associating either directly or indirectly in the same multisubunit complex, and direct, pairwise interactions were indicated by the in vivo test in yeast. In addition, SSIIa, SSIII, BEIIa, and BEIIb all comigrated in gel permeation chromatography in a high molecular mass form of approximately 600 kD, and SSIIa, BEIIa, and BEIIb also migrated in a second high molecular form, lacking SSIII, of approximately 300 kD. Monomer forms of all four proteins were also detected by gel permeation chromatography. The 600- and 300-kD complexes were stable at high salt concentration, suggesting that hydrophobic effects are involved in the association between subunits.